2019
DOI: 10.1039/c9ra01902b
|View full text |Cite
|
Sign up to set email alerts
|

The solid-state proton NMR study of bone using a dipolar filter: apatite hydroxyl contentversusanimal age

Abstract: Mineral hydroxylation in whole bone can be accurately studied using proton MAS NMR with a multiple-pulse dipolar filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 78 publications
(129 reference statements)
0
13
0
Order By: Relevance
“…With rapid advances in the magic-angle spinning (MAS) probe technology, proton-detected solid-state NMR has attracted dramatic attention in the structural characterization of small molecules, 8−12 proteins, 13−27 nuclear acids, 28−30 and bones. 31,32 Proton detection provides not only high sensitivity per unit mass but also long distances due to the high 1 H gyromagnetic ratio. Proton detection has evolved from highly 1 H-diluted samples to fully protonated samples with increasing MAS rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid advances in the magic-angle spinning (MAS) probe technology, proton-detected solid-state NMR has attracted dramatic attention in the structural characterization of small molecules, 8−12 proteins, 13−27 nuclear acids, 28−30 and bones. 31,32 Proton detection provides not only high sensitivity per unit mass but also long distances due to the high 1 H gyromagnetic ratio. Proton detection has evolved from highly 1 H-diluted samples to fully protonated samples with increasing MAS rates.…”
mentioning
confidence: 99%
“…Using solid-state NMR to elucidate protein structures generally requires the use of 13 C– 13 C or 13 C– 15 N distances as structural constraints, which are mostly obtained via 13 C-detected experiments. These long-range distances between the low-gyromagnetic nuclei are particularly difficult to observe due to weak dipolar interactions. With rapid advances in the magic-angle spinning (MAS) probe technology, proton-detected solid-state NMR has attracted dramatic attention in the structural characterization of small molecules, proteins, nuclear acids, and bones. , Proton detection provides not only high sensitivity per unit mass but also long distances due to the high 1 H gyromagnetic ratio. Proton detection has evolved from highly 1 H-diluted samples to fully protonated samples with increasing MAS rates. , Currently, the MAS frequency has gone up to 140–170 kHz using a tiny rotor with a diameter of around 0.5 mm. , The requirement for the amount of sample has been significantly reduced to the order of 0.1 mg. Consequently, proton-detected solid-state NMR under ultrafast MAS has become an indispensable tool for structural studies of these “tough” proteins or nucleic acids, which are too difficult or costly to prepare in large amounts. , …”
mentioning
confidence: 99%
“…[76] Hence, although the majority of initial solid state NMR investigations on bone and dental tissues concerned ground samples, several groups have proposed approaches to perform MAS experiments on intact ones. [73][74][75][76][77][78][79] The second issue regarding biological samples is that they need to remain hydrated to preserve their functional (and hence structural) properties. Indeed, it has been shown that bone dehydration can lead to changes in the NMR spectra, [73,74,80] meaning that strategies aiming at keeping the samples hydrated are to be privileged.…”
Section: Considerations On Sample Preparation For Nmr and Dnp Analysesmentioning
confidence: 99%
“…It must be pointed out that the last region (peaks above ~2 ppm) varies greatly depending on random changes in synthesis conditions such as the rate and order of adding reactants, stirring or vibration modes, humidity, etc. Therefore, huge variations were observed in reported results [43][44][45][46][47][48][49] as well as in the spectra shown in Figure 3 (top left in particular). It is advisable not to make quantitative claims based on the peaks in this region (please refer to the 2D HETCOR spectra discussed, below which offer far more consistent results).…”
Section: Solid-state Nmrmentioning
confidence: 95%
“…Based on the assignment of 1 H spectrum hydroxyl group corresponds to a peak at around 0.00 ppm; peaks between ~0.5 are from surface-structured water; peaks above 2 ppm are from HPO4 2-(bulk, d or surface), except for the large peak at around 5 ppm, which arises from adsorb It must be pointed out that the last region (peaks above ~2 ppm) varies greatly de on random changes in synthesis conditions such as the rate and order of adding r stirring or vibration modes, humidity, etc. Therefore, huge variations were obs reported results [43][44][45][46][47][48][49] as well as in the spectra shown in Figure 3 (top left in pa It is advisable not to make quantitative claims based on the peaks in this regio refer to the 2D HETCOR spectra discussed, below which offer far more consisten The 1D 31 P 35 kHz MAS spectra of the samples (Figure S3) are much less informative because the difference between the chemical shifts of phosphate and hydrogen phosphate is small. However, some consistent trends are noteworthy.…”
Section: Solid-state Nmrmentioning
confidence: 99%